2016
DOI: 10.1128/aac.01328-16
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of the Relative Abundance of Extended-Spectrum-Beta-Lactamase-Producing Escherichia coli in the Gut of Patients Admitted to Hospitals

Abstract: A total of 458 patients were prospectively included at hospital admission and screened for extended-spectrum-beta-lactamaseproducing (ESBL) Escherichia coli carriage in 2007 and in 2010 to 2012. A 4-fold increase in ESBL carriage (3% to 12%), a 5-fold increase in numbers of community patients among ESBL carriers, and a higher number of multiple ESBL strains was found in the 2010 to 2012 period. ESBL E. coli represented the dominant E. coli strain (relative abundance, >50%) in 10/32 (31%) of ESBL carriers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The mean relative abundance of CRE (CRE-RA) was similar to that found in other studies in Europe for community ESBL-producing E. coli [68,69] highlighting that in patients with no recent exposure to antibiotics, multidrug-resistant Enterobacterales remain subdominant. Surprisingly though, the mean CRE-RA of hospital-acquired CRE was not higher.…”
Section: Plos Onesupporting
confidence: 81%
“…The mean relative abundance of CRE (CRE-RA) was similar to that found in other studies in Europe for community ESBL-producing E. coli [68,69] highlighting that in patients with no recent exposure to antibiotics, multidrug-resistant Enterobacterales remain subdominant. Surprisingly though, the mean CRE-RA of hospital-acquired CRE was not higher.…”
Section: Plos Onesupporting
confidence: 81%
“…The other MDRO belong mainly to the ESKAPE group ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa , and Enterobacter species) (5). Likewise, those species are also opportunistic pathogens and quantitative studies of the prevalence, bacterial load and diversity of these species as well as E. coli in their natural environment, which is the digestive gut, are essential (3, 6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…So far quantitative studies of E. coli in the feces have been performed using fresh feces or rectal swabs rapidly seeded or placed in Brain Heart infusion (BHI) with glycerol and placed at −80°C (3, 6, 7). In prospective studies, these procedures are time consuming and can not be applied in numerous labs.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 86 studies included in SR1 , 75 were included in qualitative analysis 13,14,[16][17][18][19][20][21][22][23][24][25]27,28,30,[32][33][34][35][36][38][39][40][41][74][75][76][77][78][79][80][81][82][83]85,86,90,91 as two reported on repeated screening procedures (excluding two studies 34,63 ) and nine reported on screening activities in outbreak situations 15,29,31,37,42,84,[87][88][89] . Among included studies, 24 concerned routine care screenings 41,…”
Section: Description Of Screening Approachesmentioning
confidence: 99%